MITIGATING MEASURES FOR WILDLIFE MORTALITY IN AGRICULTURAL LANDSCAPES TO PREVENT ACCIDENTAL FALLS INTO OPEN WELLS IN MAHARASHTRA, INDIA: A RETROSPECTIVE STUDY - Mahendra Dhore; Kartick Satyanarayan; Smita Rajhans; S. Ilayaraja; M.V. Baijuraj; Avinash Visalkar; Akash Dolas; Srinu Srikanta Maharana; Arun A Sha (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Open wells in agricultural regions of India pose a critical, yet underreported threat to terrestrial wildlife. This study investigates incidents of wildlife falls into open wells across Pune and Ahmednagar districts of Maharashtra between 2009 and 2024. Indian leopards (Panthera pardus fusca) were the most frequently affected species, accounting for 67.6% of the 68 documented cases. Temporal trends indicate an increasing frequency, with peaks in 2019 and 2023. Other species affected include golden jackals, small Indian civets, Asian palm civets, striped hyaenas, and sambar deer. All animals were successfully rescued and released through operations led by Wildlife SOS and the Maharashtra Forest Department. Twenty-one high-risk wells were covered as part of mitigation efforts. The findings underscore the urgency for expanded, proactive programs to cover the wells to reduce wildlife mortality and foster coexistence in human-dominated landscapes.